Design of spherical TiN/Nb4N5 heterostructure as bifunctional adsorption/catalytic material for lithium sulfur batteries. (December 2022) - Li, Guochun; Zhang, Shan; Zhao, Shuo; Jiang, Xiangli; Cui, Yingxue; Lian, Jiabiao; Wang, Yong
Abstract: Lithium sulfur (Li-S) battery is the typical representative of the new generation secondary batteries, but its practical application is greatly hindered by the shuttle effect of lithium polysulfides (LiPSs) and sluggish electrochemical reaction kinetics. In this work, a spherical TiN/Nb4 N5 heterostructure is produced by nitridation of TiNb2 O7 microsphere and then used as an adsorption and catalytic material to fabricate modified polypropylene separator in Li-S batteries. Visual adsorption tests show that the TiN/Nb4 N5 heterostructure has better adsorption capacity of LiPSs than that of TiNb2 O7 microsphere precursor. The TiN/Nb4 N5 heterostructure also exhibits superior catalytic performance to accelerate the redox reaction kinetics of LiPSs conversion. The Li-S cell assembled with TiN/Nb4 N5 modified separator can deliver an initial discharge capacity of 917 mAh g −1 at 0.2 C, and a reversible capacity of 663.2 mAh g −1 after 200 cycles, higher than the cell assembled with TiNb2 O7 modified separator (555.4 mAh g −1 ) and pristine separator (385.1 mAh g −1 ). In short, this work provides a simple synthetic method to obtain a TiN/Nb4 N5 heterostructure with enhanced electrochemical performance of Li-S batteries. Graphical Abstract: ga1 Highlights: TiN/Nb4 N5 heterostructure is synthesized by nitriding TiNb2 O7 microsphere. TiN/Nb4 N5 heterostructure has strong adsorptive/catalytic conversion capability for polysulfides. Li-S cell assembled with TiN/Nb4 N5 modified separator shows excellent electrochemical performance.